PENGARUH ALAT Ã¢â‚¬Å“ASAP FILTERÃ¢â‚¬Â TERHADAP KADAR KEPEKATAN ASAP KENDARAAN BERMESIN DIESEL - Usman, Ramly (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2000)
An investigation of the influence of smoke reduction in diesel engines was carried out. A smoke filter “ASAP” has been installed between carburetors and injection pump of the tested vehicles, namely: Isuzu Panther, Minibus Toyota, and Truck Mitsubishi Fe 119. The testing procedures follow the standard of STALDAD 2.03-90 issued by the Directorate General of Land and Transportation No. AJ- 402/8/5/1990. The engines were accelerated from low to maximum speed by changing the gear from neutral to highest gear transmission. The result of the testing shows that there was reduction in percentage of smoke in the vehicles, i.e. decrease of 35.73 % for neutral transmission, and decrease of 28.86 % for gear transmission. The testing indicates that the reduction of smoke for the diesel engines on neutral transmission is more significant than in gear transmission